Determinación de antígeno prostático específico total y libre como ayuda al diagnóstico de alteraciones prostáticas benignas y malignas en hombres de 50 a 70 años que asisten al hospital andino alternativo de chimborazo en el periodo enero a junio 2015. - Chulli Guarango, Alexandra Carolina (2016)
The theme: Determination of total and free prostate-specific antigen as an aid in the diagnosis of prostate and malignant tumors benign in men 50 to 70 years attending the Andean Hospital Alternative Chimborazo in the period January to June 2015, it responds to the need to know as it affects the measurement of total and free PSA to help diagnose prostate disorders, for which we worked on the goal; determine the level of total and free prostate-specific antigen as an aid in the diagnosis of benign and malignant prostate disorders in men 50 to 70 years attending the Andean Hospital Alternative Chimborazo in the period January to June 2015, the theoretical framework was built, with the two variables, such as prostate specific antigen and prostatic diseases, the methodology used was; the deductive method of formulating the research hypothesis based on the general theory, research was explanatory, descriptive field, the population was 60 patients aged 50 to 70 years who attended the Andean Hospital Alternatively, the service laboratory, were performed the tests to determine total and free PSA, the results allowed to fulfill the objectives set and test the hypothesis, conclusions were drawn and recommendations were proposed; The main conclusion was; the results of laboratory tests to determine the dosage of total PSA and free serve to confirm presumptive diagnosis, which relates the importance of determining these analyzes to demonstrate that these tests if affect prostate pathology.